Обстеження на місці відтворення Подільської вежі та чатового бастіону Полтавської фортеці XVIII ст. - Пуголовок, Ю.О. (Археологічні дослідження в Україні, 2010)
Results of the research at the area of reconstruction of the fortifications of the 18th c. Poltava fortress on Ivanova Mountain in Poltava are published. The stages of shaping the slope related to possible rebuilding of the fortress and to conversion of the city territory in the recent time are traced.